Accounting, costing and strategies in paddy cultivation - Mustafa, Hasri (UM Press, 2019)
For the last forty years, M has been traditionally a paddy cultivator with a modest income. With his 56th birthday approaching, M has decided that it is time to break away from his paddy life and live with his son in the nearby town. He has no desire to sell his 15 relongs paddy of fields though, and does not wish to rent it to a stranger. He has found the solution to his problem by allowing I, his old primary school friend, to work on his paddy field with a 40:60 profit sharing for one cultivation season. ‘I’ has proved to be amenable to the idea, and has agreed in principle to get so involved in this plan but he has problem to assess the potential of paddy as a main source of income. Although he has been working for three years on his 6 relongs, he has never taught with the idea of getting a whole-paddy income analysis. He believes in practical good financial reward is just for hard work worker. Meanwhile C, a neighbour of M has shown interest to rent M’s 15 relongs. C works with 20 rented relongs and he is thinking to produce more paddy crops with the benefits of averaging costs. C has a particularly good relation with a bank manager in a nearby town and has learned from his Chinese counterparts that renting relong for paddy is a good business. C was advised to keep records often so to provide little data for analysis. How would M, C and I do? What solution capable to offer to M from the perspectives of C and I? The above cases of M, I and C are common in small-scale paddy cultivation. Our chief concern is to determine how each of them managed to earn some general level of acceptance of income based on not the quality of paddy production or the market price of paddy which are not capable to control by farmers, but on the costs and activities of paddy paddock preparation, paddy seeds plantation, paddy growing and caring, paddy harvesting time and paddy delivery. Accounting, Costing and Strategies in Paddy Cultivation should be read by every professional accountant, farmer, head of the family, student, researcher, policy maker and environmentalist.